The relationship betweeen macroeconomic factors and the prices of gold in Malaysia / Fatin Nur Shafiqah Nizam - Nizam, Fatin Nur Shafiqah (2019)
This paper examined factors that affecting the prices of gold in Malaysia. Among macroeconomic factors for this study are currency exchange rates (MYR per USD), stock market index (KLCI), inflation rates (CPI) and silver prices in monthly period for ten years from 2009 to 2018. The objective of this study is to examine whether each of the independent variables have a positive or negative relationship with gold prices (Kijang Emas) in Malaysia. This study used Multiple Linear Regressions (MLR) to determine macroeconomic factors affecting the gold price in Malaysia and correlation coefficient will analyze the relationship among variables and all the data were analyzed using STATA 14.